Menkes disease complicated by concurrent Koolen‐de Vries syndrome (17q21.31 deletion). Issue 8 (28th June 2019) - Woodfin, Taylor; Stoops, Christine; Philips, Joseph B.; Lose, Edward; Mikhail, Fady M.; Hurst, Anna
Abstract: Background: Koolen‐de Vries (KdV) syndrome is caused by a 17q21.31 deletion leading to clinical symptoms of hypotonia and developmental delay and can present with abnormal hair texture. Menkes disease is an X‐linked recessive inherited disease caused by pathogenic variants in ATP7A, which leads to profound copper deficiency. Method: We identified an infant male who presented with prematurity, hypotonia, and dysmorphic features for whom a family history of clinical Menkes disease was revealed after discussion with the clinical genetics team. Results: Although initial first‐tier genetic testing identified Kdv syndrome (17q21.31 syndrome), the family history led the team to consider a second diagnostic possibility, and testing of ATP7A revealed a pathogenic variant (c.601C>T, p.R201X). Conclusion: Menkes disease and KdV syndrome may both present with hypotonia and abnormal hair, in addition to seizures and failure to thrive. While these genetic conditions have overlapping clinical features, they have different natural histories and different therapeutic options. Here, we report on a patient affected with both disorders and review the diagnostic and therapeutic difficulties this presented. Abstract : Koolen‐de Vries syndrome is caused by a 17q21.31 deletion leading to clinical symptoms of hypotonia and developmental delay and can present with abnormal hair texture. Menkes disease is an X‐linked recessive inherited disease caused by pathogenic variants in ATP7A, which leads to profound copper deficiency and may present with hypotonia and abnormal hair, in addition to seizures and failure to thrive. While these genetic conditions have overlapping clinical features, they have different natural histories and different therapeutic options. Here, we report on a patient affected with both disorders and review the diagnostic difficulties this presented.